Biofortification: The evidence - Birol, Ekin; Foley, Jennifer; Aytekin, Destan (International Food Policy Research Institute, 2021)
The scientific body of evidence supporting biofortification spans over two decades. This document provides a summary of peer-reviewed research that has proven biofortification to be an efficacious, cost-effective, and scalable innovation that can play a pivotal role in transforming food systems to deliver affordable and accessible nutritious food for all.